2002
DOI: 10.1046/j.0021-8790.2001.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Helping does not enhance reproductive success of cooperatively breeding rufous vanga in Madagascar

Abstract: Summary1. In many studies on cooperative breeding, helping by auxiliary individuals is considered to enhance the reproductive success of breeders. However, confounding factors other than helping could cause the differences. 2. The endemic Madagascan rufous vanga Schetba rufa (Vangidae) is known as a cooperatively breeding species. In order to evaluate the effect of helping in this species, we compared the reproductive success of breeding pairs helped by auxiliary birds, and pairs breeding alone, based on a 6-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…However, unless the cost of expelling subordinates is large, the expected decline in breeder fitness should be slight. Several correlational and experimental studies of helping have found that the presence of helpers has little effect on the reproductive success of breeders (see, for example, Magrath & Yezerinac 1997;Legge 2000;Eguchi et al 2002) or even a negative effect (Legge 2000). In these systems, auxiliaries at the nest were observed to invest substantially in helping.…”
Section: Discussionmentioning
confidence: 99%
“…However, unless the cost of expelling subordinates is large, the expected decline in breeder fitness should be slight. Several correlational and experimental studies of helping have found that the presence of helpers has little effect on the reproductive success of breeders (see, for example, Magrath & Yezerinac 1997;Legge 2000;Eguchi et al 2002) or even a negative effect (Legge 2000). In these systems, auxiliaries at the nest were observed to invest substantially in helping.…”
Section: Discussionmentioning
confidence: 99%
“…Breeders may also benefit indirectly if retained offspring are subsequently more likely to survive and reproduce themselves (Cockburn 1998). However, many cooperative systems do not exhibit clear reproductive or survival benefits of helper retention to breeding individuals , Eguchi et al 2002, Cockburn et al 2008, Varian-Ramos et al 2010. Paradoxically, helper retention can be detrimental to breeder fitness in some cases (Mulder et al 1994, Dierkes et al 1999, Double and Cockburn 2003, Webster et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, helpers have been shown to vary widely in the amount of care that they provide (Heinsohn & Legge 1999;Cant & Field 2001), but correlating helper number with offspring production does not allow for variation in helping effort (Magrath & Yezerinac 1997;Cockburn 1998). The limitations of correlational studies were highlighted in a study of rufous vangas (Schetba rufa), where a positive relationship between helper number and offspring production disappeared after controlling for variation in territory quality, breeder experience and helper effort (Eguchi et al 2002).…”
Section: Introductionmentioning
confidence: 99%